2014
DOI: 10.12691/jfnr-2-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rehydration Ratio on the Quality of <i>Auricularia auricula-judae</i> Mushroom

Abstract: This Study aimed to investigate the rehydration ratio, temperatures, times, amount of leaching of polysaccharide content and storage (CFU) of A. auricula-judae mushroom. Five rehydration temperatures (25, 40, 60, 80 and 100°C) and the water immersion time (10, 20, 30, 40, 50, 60 minutes) were used. The highest rehydration ratio 9.53%as observed in the soaking temperature of 100 • C whereas the lower rehydration ratio 5.65% obtained at 25 • C correspondingly. Whereas the polysaccharide content result revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Rehydration is the process of restoring the lost water to the dehydrated produce, and the rehydration ratio is affected by the degree of food cellular and structural damage caused by drying process. Thus rehydration ratio is generally used to evaluate the dehydration art (Khaskheli et al, ). Higher rehydration ratio indicates a better internal structure in the product.…”
Section: Resultsmentioning
confidence: 99%
“…Rehydration is the process of restoring the lost water to the dehydrated produce, and the rehydration ratio is affected by the degree of food cellular and structural damage caused by drying process. Thus rehydration ratio is generally used to evaluate the dehydration art (Khaskheli et al, ). Higher rehydration ratio indicates a better internal structure in the product.…”
Section: Resultsmentioning
confidence: 99%
“…, 2017). The temperature and duration of water immersion during rehydration can compromise the safety of wood ear mushrooms (Khaskheli et al. , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Ajis et al. , 2017; Khaskheli et al. , 2014) have indicated that improper rehydration practices of dried mushrooms, such as prolonged rehydration at room temperature, can create opportunities for the growth of foodborne pathogens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations